Modeling Direct Runoff Hydrograph Using GAMMA Distribution Function - Patil, P V; Atre, A A; Chunale, G L; Bote, N L; Gutal, G B; Patil, V P (Journal of Agricultural Engineering, 2008)
Gamma distribution function can have variety of shapes including single peaked positively skewed graph having unit area under the curve, which perfectly matches the graphical presentation of unit hydrograph. The shape and scale parameters can be evaluated from the observed peak runoff rate and time to peak duration by iterative method. Unit hydrograph assumes uniformly distributed storm over the entire area of the watershed hence, a small experimental watershed of 0.12 sq. km at Zonal Agricultural Research Station, Shenda Park, Kolhapur (India) was considered for the application of model. In this paper a different approach of evaluation of Alpha and Beeta have been given with computer program in C language, which will be more effective in computation of shape and scale parameters of Gamma distribution function for modeling the unit hydrograph and then converting to the direct runoff hydrograph. The results of regeneration of direct runoff hydrograph shows very good fit of the observed and computed peak flow and volume under direct runoff hydrograph. The average values ofshape and scale parameters also gave better fit of direct runoff hydrograph.